Synthesis, structural and spectroscopic characterization of thallium(I) acesulfamate - Baran, Enrique José (2015)
The new acesulfamate salt, TlC4H4NO4S, was prepared by reaction of acesulfamic acid and thallium(I) carbonate in aqueous solution. Its crystal and molecular structure was determined by single crystal X-ray diffraction methods. The substance crystallizes in the monoclinic space group P21/a, with unit cell parameters a = 7.5844(4) Å, b = 9.7268(5) Å, c = 10.8105(5) Å, β = 105.174(6)°, and Z = 4 molecules per unit cell, and is isostructural with the corresponding sodium, potassium, rubidium and cesium salts. The FTIR and Raman spectra of the compound are also recorded and briefly discussed.